From Jesus to the Gospels : interpreting the New Testament in its context - Koester, Helmut, 1926- (Minneapolis : Fortress Press, 2007)
Helmut Koester offers a lifetime's insights into the message of the historical Jesus and the traditions, practices, and trajectories that shaped the Gospels and other early Christian literature including 'Q' and the Gnostic Gospels.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Person and offices; Bible: Gospels -- Criticism, interpretation, etc